MENINGKATKAN MINAT SISWA KELAS X - C TERHADAP PEMBELAJARAN BOLA VOLI DI SMK NEGERI 11 MEDAN TAHUN AJARAN 2019/2020 - Omri Sembiring (Universitas Islam Negeri (UIN) Sumatera Utara, 2021)
The research subjects were 32 students of class X-C consisting of 13 male students and 19 female students. The data analysis techniques are: 1) the level of student mastery, 2) complete learning. Based on the results of the study, it shows that the average value obtained by students is above 65. Where it can be seen from the average values of students in the Pre-Test (Initial Test) 45.31% then there is an increase in student interest in learning in the first cycle of 13 .12% to 58.43% and then in the second cycle there was an increase in student interest in learning by 20.63% to 79.06% so that the completeness value was 90.62% in the second cycle. It can be concluded that in order to increase the interest of class XC students in Volleyball Learning at SMK Negeri 11 Medan in the 2019/2020 academic year